Best Answer

7x - 9y = -63.

When y = 0 then the resultant answer provides the x intercept.

7x - 0 = -63 : x = -9

When x = 0 then the resultant answer provides the y intercept.

0 - 9y = -63 : y = 7

Alternatively, to ascertain the y intercept convert the equation into the form y = mx + c, c is the y intercept.

7x - 9y = -63 : -9y = -7x -63 : 9y = 7x + 63 : y = 7/9x + 7

Study guides

☆☆

Q: What is the intercepts 7x-9y equals -63?

Write your answer...

Submit

Still have questions?

Related questions

what equals 63

what x3 equals 63 is:21x3=63

63-84 equals = -21

Slope: -1 intercepts: (0,1000),(1000,0)

y = -xBoth intercepts are at the origin. From there, the line slopes up to the leftand down to the right.

It is 6000.

Each of these factor pairs (multiply the numbers in parentheses) equals 63: (1, 63) (3, 21) (7, 9)

-9 times 7 equals -63.

X intercept: -5 Y intercept: +3

63 centimeters equals how many millimeters

12

63 ___ 100

People also asked